2008
DOI: 10.2337/db07-1515
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Oral Antidiabetic Drugs With Hepatic Uptake Transporters

Abstract: OBJECTIVE-The uptake of drugs into hepatocytes is a key determinant for hepatic metabolism, intrahepatic action, their subsequent systemic plasma concentrations, and extrahepatic actions. In vitro and in vivo studies indicate that many drugs used for treatment of cardiovascular diseases (e.g., oral antidiabetic drugs, statins) are taken up into hepatocytes by distinct organic anion transporters (organic anion transporting polypeptides [OATPs]; gene symbol SLCO/SLC21) or organic cation transporters (OCTs; gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 39 publications
7
66
0
3
Order By: Relevance
“…Because of their ubiquitous distribution and their wide activity range as transporters of several drugs, the role of Oatp/OATP proteins in drug disposition, bio-distribution and absorption is emerging (van Montfoort et al, 2003;Faber et al, 2003;Mizuno et al, 2003;Gerloff, 2004;Niemi, 2007;Bachmakov et al, 2008). This study presents a framework for similar studies to be carried out in ticks.…”
Section: Discussionmentioning
confidence: 95%
“…Because of their ubiquitous distribution and their wide activity range as transporters of several drugs, the role of Oatp/OATP proteins in drug disposition, bio-distribution and absorption is emerging (van Montfoort et al, 2003;Faber et al, 2003;Mizuno et al, 2003;Gerloff, 2004;Niemi, 2007;Bachmakov et al, 2008). This study presents a framework for similar studies to be carried out in ticks.…”
Section: Discussionmentioning
confidence: 95%
“…Roth et al (2011) reported that green tea catechins epicatechin gallate and epigallocatechin gallate significantly inhibited OATP2B1-mediated E3S uptake. Several flavonoids, silymarin flavonolignans, and antidiabetic drugs have also been reported to inhibit OATP2B1 in vitro (Bachmakov et al, 2008;Klatt et al, 2013;Kock et al, 2013;Li et al, 2014;Mandery et al, 2010). These reports demonstrated that OATP2B1 could interact with a wide range of natural products.…”
Section: Introductionmentioning
confidence: 92%
“…Generation and validation of HEK-OATP1B1, HEK-OATP1B3, and HEK-OATP2B1 cells as well as the cells expressing the OATP1B1 variant *5 have been described before (Bachmakov et al, 2008). HEK293 cells stably expressing the OATP1B1 variants OATP1B1*1b and OATP1B1*15 and HEK293 cells expressing human OATP1A2 and OATP4A1 were established as described previously .…”
Section: Chemicalsmentioning
confidence: 99%